Design, Construction, and Performance Evaluation of an Evaporative Cooling System for Tomatoes Storage (Agricultural Engineering, 2020)
An evaporative cooling system was designed and constructed to increase the shelf life of stored vegetables. The evaporative cooler was tested and evaluated using freshly harvested roma tomatoes. The equipment operates on the principle of evaporative cooling which increased the relative humidity and decreased temperature in the preservation chamber. The storage system was made up of wood of 25.4 mm thickness. A side of the system is made of jute sack, which was moistened with water flowing through a series of perforated pipes from a reservoir located at the top of the storage system. The water flowed under gravity. The relative humidity and temperature of the tomatoes were analyzed using tinytag humidity, temperature data logger. The weight loss of the tomatoes was also analyzed using a dial gauge scale. The results revealed that there was significant difference in using the evaporative cooling system for storing tomatoes as compared to ambient conditions. The average cooling efficiency was found to be 81%. The average temperature achieved in the cooling system dropped to an average of 23℃ when compared to the average ambient temperature of 33℃, and the relative humidity also increased up to 99% when compared to the average ambient of 59%. The analysis of the evaporative cooling system showed that tomatoes can be stored for more than 6 days with negligible changes in weight, colour and firmness as compared to those under ambient condition, which deteriorated after day 3. The evaporative cooling system was found to be effective and hence can be used by farmers, households, and tomato processing factories for short term storage of fresh tomatoes.